Structural Features of China's Industrial Pollution Inequality: A Spatial-Temporal Distribution Perspective - Luo, Jin; Wang, Yuan; Zhu, Lin; Jiang, Pei-Pei; He, Yan-Min; Hao, Ting-Ting (Frontiers in Environmental Science, 2022)
With growing concerns about the allocation inequality of environmental benefits and pollution, it is crucial to investigate whether a special characteristic of China’s environmental inequality has emerged. The present study aims to elucidate the regional spatial features of industrial pollution inequality (IPI) (waste gas, wastewater, and solid waste measured by the Theil index separately) and their relevance to national territorial space planning strategies. Furthermore, we make a novel attempt to develop an integrated framework that employs a developed-Kaya identity with the Logarithmic Mean Divisia Index method to uncover the driving force of IPI disparities. We make use of the data published recently by the provincial panel of China, during the period 2000–2015. Based on this information, we found notable spatial-temporal heterogeneity in China's IPI, highly correlated to China's core national territorial space planning strategy, the “T-shaped” spatial development strategy. The empirical results support the “structural features” hypothesis in IPI for China. In particular, the Coastal Region has a great edge in industrial pollution equality. In most provinces in the Inland Corridor along the Yangtze River, the trend of IPI has been alleviated to some extent. However, provinces further inland that are off-side the two axes of “T-shaped” spatial development strategy have to respond to the two-fold challenge of the exacerbated trend in IPI both within and between the regions. Our findings also indicate that the effect of technological inequality is the main driving force for IPI in the earlier stage of development. However, effects of economic inequality together with that of economic structure inequality manifest in the middle or transition period and the economic inequality effect is the determinant in the later stage of development. Additionally, contributions of size effect and inequality effect are changeable over development process, economic inequality effect outweighs the economic size effect for IPI in more developed districts or districts in higher developing phases. These findings may help the government incorporate environmental equality goals into regional policies and contribute to the emerging literature on environmental inequality.